Drilling Strategy for Thick Carbon Fiber Reinforced Polymer Composites (CFRP): A Preliminary Assessment - Ahmad Sobri, Sharizal; Heinemann, Robert; Whitehead, David; Shuaib, Norshah Afizi (ITB Journal Publisher, LPPM ITB, 2018)
Carbon fiber reinforced polymer or CFRP composites are the epitome of high-performance materials in lightweight design. However, their machinability can be problematic due to non-homogenous and anisotropic material properties. This preliminary assessment emphasizes drilling strategy by using mechanical drilling and laser machining on 25.4 mm thick CFRP, which has not been investigated so far. In mechanical drilling, three drilling strategies were applied with the same parameters in order to assess the feasibility of drilling thick CFRP. The laser machining experiments were conducted to identify the potential of fiber laser machines to cut thick CFRP due to their superior laser beam quality. The results showed that choosing the appropriate drilling strategy in mechanical drilling is essential for reducing damage when drilling thick CFRP. Significant damage occurred in all experiments. The results are useful to define the relationships between machining parameters related to mechanical/laser drilling and hole/cut quality.